Performance calculation of high speed solid rotor induction machine - Papini, Luca (2018)
Solid rotor induction machines are suitable for applications which require robustness, reliability and high rotational speed. A literature review of high speed technologies is initially presented. The current limitation and challenges are detailed based on a wide collection of data. The multi-physics aspect related with electrical machines for high speed applications are discussed providing a summary of the current state of the art. The main aim of the research was to develop a multi-physic computational environment for the design and analysis of solid rotor induction machines. The electromagnetic, thermal, structural and rotor dynamics models have been developed targeting reduced computational time and accurate predictions. Numerical techniques are proposed based on the discretisation of the computational domain. The different disciplines are linked together providing a flexible and powerful tool for the characterisation of solid rotor induction machine. Another objective was to investigate the impact of the rotor material on the electromagnetic performances of the machine. Finite Element simulation are used to account for the non linear magnetic properties. The impact on the equivalent circuit parameter is discussed and general criteria for material selection presented. Three dimensional finite element calculation are p erformed targeting the validation of the end region correction factor and select the rotor length. The performances of a 120 [kW]−25000 [rpm] solid rotor machine are compared with a caged rotor induction machine for waste heat recovery application.